MINUMAN FUNGSIONAL TERIPANG PASIR (Holothuria scabra) DAN TERIPANG HITAM (Holothuria atra) - Elfath, Nurul Afifah; Putri, R. Marwita Sari; Apriandi, Azwin (Marinade, 2019)
This research was conducted in two stages: Preparation of raw materials for Holothuria scabra and Holothuria atra. and formulation of functional beverage products. The objectives of this study are knowing the bioactive compounds such as saponins and antioxidants in functional drinks Holothuria scabra and H. atra. The results of this study concluded that the best functional formulations of Holothuria scabra and H. atra drink based on organoleptic tests were functional drink with MFKT3 formulation with concentrations of Holothuria scabra and H. atra 30%, 20% rosella, 10% ginger, 10% lemongrass, 10 kalamansi orange %, sugar 20%. The results of the analysis of H. scabra and H. atra functional drinks in the nutritional component of water content were 89.17% and 89.16%, ash content 5.19% and 1.93%, protein content 5.06% and 7.74%, fat content 0.29% and 0.29%, carbohydrate content 0.27% and 0.87%. The antioxidant activity found in functional drinks of Holothuria scabra and H. atra is very weak because the IC50 value is greater than 0.20 mg/ml or 200 ppm which is 1621 ppm. Saponins in functional drink extracts are identified by the formation of foam or foam.